The Effect of Work Creativity, Resilience and Job Embeddedness on intention to leave and employee performance of PT Romi Violeta Sidoarjo East Java - Kusuma, Yoga Pradipta Angga; Mujanah, Siti; Ridwan, M. Sihab (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study was to analyze the effect of work creativity, resilience, and job embeddedness on intention to leave and employee performance at PT Romi Violeta. This research is a quantitative research with a sample of 98 respondents from employees of PT Romi Violeta. The data analysis technique used is the partial least square (PLS) method. The results show that work creativity has a significant negative effect on intention to leave, resilience has a significant negative effect on intention to leave, job embeddedness has a significant negative effect on intention to leave, work creativity significant positive effect on employee performance, resilience has a significant positive effect on employee performance, job embeddedness has a significant positive effect on employee performance, intention to leave has a significant positive effect on employee performance.